2018
DOI: 10.1063/1.5052683
|View full text |Cite
|
Sign up to set email alerts
|

On the proposed martensitic-like structural transformation in V, Nb, and Ta

Abstract: A recent announcement, after anomalies in the thermal expansion, of a previously unknown martensitic transformation in pure Nb, Ta and V is discussed in the light of anelastic measurements on Nb samples with comparable purities. It results that the effects of the alleged transformation on the anelastic spectra would be at least three orders of magnitude smaller than in typical martensitic transformations. A possible alternative explanation for the observed anomalies is proposed in terms of precipitation of unn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…It was also suggested that the structural transition could be suppressed by interstitial oxygen in previous studies and, hence, the hydrogen contamination does not play a role. However, a presence of this martensitic phase transition in V was later questioned [31] and obviously an additional verification by more sensitive experimental techniques is required. Furthermore, the anomaly in electrical resistivity was not detected by Jung et al on high-purity samples containing 28 at.…”
Section: Introductionmentioning
confidence: 99%
“…It was also suggested that the structural transition could be suppressed by interstitial oxygen in previous studies and, hence, the hydrogen contamination does not play a role. However, a presence of this martensitic phase transition in V was later questioned [31] and obviously an additional verification by more sensitive experimental techniques is required. Furthermore, the anomaly in electrical resistivity was not detected by Jung et al on high-purity samples containing 28 at.…”
Section: Introductionmentioning
confidence: 99%